Consumption-based biodiversity footprints – Do different indicators yield different results?. (August 2019) - Marquardt, Sandra G.; Guindon, Michael; Wilting, Harry C.; Steinmann, Zoran J.N.; Sim, Sarah; Kulak, Michal; Huijbregts, Mark A.J.
Graphical abstract: Highlights: We linked economic relationships of regions to four biodiversity indicators. Alpha diversity results show more diverse spread of countries than gamma. Correlation between footprints and prosperity mainly visible for alpha diversity. Both diversity dimensions (alpha and gamma) should be used in footprint analyses. Abstract: Land use related to human consumption patterns leads to significant loss of biodiversity. Here, the implications of using different indicators in the calculation of biodiversity footprints caused by land use were analyzed. Footprints refer to the impacts related to the net consumption in a region. We calculated biodiversity footprints for 140 regions in the world with an environmentally-extended multi-regional input-output (EEMRIO) model. The EEMRIO links economic activities from the Global Trade Analysis Project (GTAP) database with land use and four indicators of biodiversity loss. We included three alpha diversity indicators (loss of mean species abundance, relative abundance and relative species richness) and one indicator of gamma diversity (vulnerability-weighted relative species richness loss). While the three alpha diversity indicators reflect local diversity within a site, the gamma diversity indicator captures global diversity by weighting regional species richness with species' extinction vulnerability in a region. We found that the three alpha diversity footprints show close alignment (rS > 0.93), while there was limited convergence between alpha and gamma diversity footprints (rS < 0.22). The alpha diversity indicators identified a diverse set of regions with high per capita consumption-based biodiversity footprints across the globe, while the gamma diversity indicator emphasized human consumption patterns threatening particularly tropical biodiversity. Although all footprints are positively related to rising household expenditure, this relationship was weaker and highly uncertain for the gamma diversity footprints. The alpha-based footprints also showed a negative relationship with population density, while the gamma-based footprint was not related to population density. Our results highlight the relevance of including both alpha and gamma diversity indicators in land-based biodiversity footprint calculations.